ISSUES OF ISLAMIC BANKING SYSTEM FORMATION ON THE EXAMPLE OF POST-SOVIET STATES - S. Sharipov (Вестник университета)
The relevance of forming an alternative banking system in the post-Soviet States were considered, taking into account the global macroeconomic situation. In the course of solving the problem the causes and patterns of development of the Islamic banking sector in the post-Soviet space were revealed. The issues of reforming the legislative basis in periodically changing conditions of foreign policy were involved. The process of formation the Islamic banking system and statistical indicators of the formation an alternative banking system in the Republics Kazakhstan, Tajikistan and other post-Soviet States were explored.